Obesogens beyond vertebrates: lipid perturbation by tributyltin in the crustacean daphnia magna - Jordão, Rita (2015)
Background: The analysis of obesogenic effects in invertebrates is limited by our poor knowledge of the regulatory pathways of lipid metabolism. Recent data from the crustacean Daphnia magna points to three signaling hormonal pathways related to the molting and reproductive cycles [retinoic X receptor (RXR), juvenile hormone (JH), and ecdysone] as putative targets for exogenous obesogens. Objective: The present study addresses the disruptive effects of the model obesogen tributyltin (TBT) on the lipid homeostasis in Daphnia during the molting and reproductive cycle, its genetic control, and health consequences of its disruption. Methods: D. magna individuals were exposed to low and high levels of TBT. Reproductive effects were assessed by Life History analysis methods. Quantitative and qualitative changes in lipid droplets during molting and the reproductive cycle were studied using Nile red staining. Lipid composition and dynamics were analyzed by ultra-performance liquid chromatography coupled to a time-of-flight mass spectrometer. Relative abundances of mRNA from different genes related to RXR, ecdysone, and JH signaling pathways were studied by qRT-PCR. Results and Conclusions: TBT disrupted the dynamics of neutral lipids, impairing the transfer of triacylglycerols to eggs and hence promoting their accumulation in adult individuals. TBT’s disruptive effects translated into a lower fitness for offspring and adults. Co-regulation of gene transcripts suggests that TBT activates the ecdysone, JH, and RXR receptor signaling pathways, presumably through the already proposed interaction with RXR. These findings indicate the presence of obesogenic effects in a nonvertebrate species.